Intracellular and extracellular biomarkers predictive of response to anti-cancer treatments for breast and prostate cancer - Corcoran, Claire (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2013)
Cancer remains one of the leading causes of death worldwide. Breast and prostate cancer are the most frequently diagnosed cancers among women and men, respectively. Despite some breakthroughs in their treatment, innate or acquired-resistance hinders the continued success of some treatments. Through the initial use of breast cancer cell lines with acquired- or innate-resistance to trastuzumab, lapatinib and later assessing neratinib and afatinib, this PhD investigated the mechanisms behind resistance to these therapies. Similarly, the mechanisms involved in regulating docetaxel-resistance in prostate cancer cell lines were also investigated. The second focus of this PhD involved testing the hypothesis that the extracellular environment may carry biomarkers representative of their cells of origin, thus offering the potential of identifying biomarkers in a minimally- invasive manner.
Keywords: Pharmacy & Pharmaceutical Sciences, Ph.D.; Ph.D. Trinity College Dublin